The Intestinal Roundworm Ascaris suum Releases Antimicrobial Factors Which Interfere With Bacterial Growth and Biofilm Formation - Midha, Ankur; Janek, Katharina; Niewienda, Agathe; Henklein, Petra; Guenther, Sebastian; Serra, Diego O.; Schlosser, Josephine; Hengge, Regine; Hartmann, Susanne (Frontiers in Cellular and Infection Microbiology, 2018)
Ascariasis is a widespread soil-transmitted helminth infection caused by the intestinal roundworm Ascaris lumbricoides in humans, and the closely related Ascaris suum in pigs. Progress has been made in understanding interactions between helminths and host immune cells, but less is known concerning the interactions of parasitic nematodes and the host microbiota. As the host microbiota represents the direct environment for intestinal helminths and thus a considerable challenge, we studied nematode products, including excretory-secretory products (ESP) and body fluid (BF), of A. suum to determine their antimicrobial activities. Antimicrobial activities against gram-positive and gram-negative bacterial strains were assessed by the radial diffusion assay, while effects on biofilm formation were assessed using the crystal violet static biofilm and macrocolony assays. In addition, bacterial neutralizing activity was studied by an agglutination assay. ESP from different A. suum life stages (in vitro-hatched L3, lung-stage L3, L4, and adult) as well as BF from adult males were analyzed by mass spectrometry. Several proteins and peptides with known and predicted roles in nematode immune defense were detected in ESP and BF samples, including members of A. suum antibacterial factors (ASABF) and cecropin antimicrobial peptide families, glycosyl hydrolase enzymes such as lysozyme, as well as c-type lectin domain-containing proteins. Native, unconcentrated nematode products from intestine-dwelling L4-stage larvae and adults displayed broad-spectrum antibacterial activity. Additionally, adult A. suum ESP interfered with biofilm formation by Escherichia coli, and caused bacterial agglutination. These results indicate that A. suum uses a variety of factors with broad-spectrum antibacterial activity to affirm itself within its microbe-rich environment in the gut.